Remotely Actuated Magnetic Nanocarpets for Bone Tissue Engineering: Non‐Invasive Modulation of Mechanosensitive Ion Channels for Enhanced Osteogenesis. (9th July 2022) - Unnithan, Afeesh Rajan; Sasikala, Arathyram Ramachandra Kurup; Shrestha, Bishnu Kumar; Lincoln, Alex; Thomson, Thomas; El Haj, Alicia J.
Abstract: Non‐invasive approaches using remotely controllable nanomaterials have demonstrated their potential ability to enhance treatment efficacy in regenerative medicine and tissue repair. Although magnetic nanoparticles (MNPs) have been used for multiple healthcare applications where their remote control properties can show significant advances, enhanced surface functional groups, and electrical properties would expand their capabilities. To address this, in this study, MNPs incorporated Graphene Oxide (GO) based nanocomposites (GOMNPs) are developed and functionalized with TREK1 and Piezo1 antibodies to specifically target the respective mechanosensitive ion channels. Magnetic ion channel activation (MICA) technology is used to remotely activate MG63 osteoblast‐like cells tagged with these functionalized GOMNPs. Remote activation of mechanotransduction pathways shows significant upregulation in osteogenic gene expression as well as enhanced alkaline phosphate activity and calcium mineralization with enhanced bone formation. The development of a GOMNP composite has extensive applicability for future clinical translation. Abstract : Schematic illustration showing the magnetic ion channel activation (MICA) based remote cell stimulation using the functionalized Graphene Oxide based nanocomposites (GOMNPs) nanocarpets. GOMNPs are functionalized with specific antibodies to target the mechanosensitive Piezo1 and TREK1 ion channels and then MICA bioreactor is used to remotely activate the cells tagged with these functionalized GOMNPs for enhanced osteogenesis.